ANALISIS KINERJA OMBUDSMAN PROVINSI RIAU - Jesika Puteri; Nurmala Sari (Jurnal Administrasi Publik dan Bisnis, 2023)
The Ombudsman is a public complaints institution formed to realize "Good Governance" and "Clean Government" local governments are required to be able to provide services to the public in an effective, efficient and accountable manner. The purpose of this study was to analyze the performance of the Riau Province Ombudsman in completing community reports. The method used in this research is descriptive qualitative. The indicators used to assess performance in this study are productivity, service quality, responsiveness, responsibility, and accountability. In addition, it is also seen from the supporting factors and inhibiting organizational performance. The results showed that the productivity of the Ombudsman Representative of the Republic of Indonesia in Riau Province had not been maximized because the completion of reports that had not been owned by the community had not yet reached the target. Factors hindering performance are the lack of quantity and quality of human resources in completing reports, the absence of work system mechanisms, lack of facilities and infrastructure, limited budgets, lack of public knowledge about the existence of an Ombudsman in Riau Province, as well as the leadership and performance Ombudsman driving team.